2020
DOI: 10.1016/j.cjtee.2020.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of closed subtalar joint dislocation: A case report and literature review

Abstract: Subtalar dislocation is defined as a separation of the talocalcaneal and talonavicular articulations, commonly caused by high-energy mechanisms, which include falls from height, motor vehicle crashes, and twisting leg injuries. The dislocations are divided into medial, lateral, anterior, and posterior types on the basis of the direction in which the distal part of the foot has shifted in relation to the talus. The most common type is medial dislocation resulted from inversion injury. Subtalar dislocation may a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
(14 reference statements)
0
13
0
Order By: Relevance
“…The overall rate of complications is 20% and is directly related to the severity of injury, open injuries, and the extent of the fractures. Postoperative osteonecrosis of the body of the talus and subtalar stiffness are the most common complications 6. Instability after reduction is another possible complication, which can be avoided by short-term immobilization 7…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall rate of complications is 20% and is directly related to the severity of injury, open injuries, and the extent of the fractures. Postoperative osteonecrosis of the body of the talus and subtalar stiffness are the most common complications 6. Instability after reduction is another possible complication, which can be avoided by short-term immobilization 7…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative osteonecrosis of the body of the talus and subtalar stiffness are the most common complications. 6 Instability after reduction is another possible complication, which can be avoided by short-term immobilization.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with this type of dislocation show severe soft tissue damage [ 6 ]. This injury is rare due to strong ligaments connecting the talus and the calcaneum and due to the biomechanical qualities of the ankle [ 2 , 7 ]. In a study conducted by Perugia et al, the AOFAS (American Orthopedic Foot and Ankle Score) scale score showed no statistically significant difference between the medial and lateral STJD at seven-year follow-up [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mean age at treatment was 32.54 years, ranging from 16 to 71 years [23,32]. The total number of patients for each study ranged between one and 10 [22,[24][25][26][27][28][29][30][31][32]. In one paper, the affected ankle was not specified (for a total of four patients); of the remaining 22 patients, the right ankle was affected 15 times (68.18%) and the left ankle seven times (31.82%).…”
Section: Patient Populationmentioning
confidence: 99%
“…The mean score was 86, with a range from 66 to 100. Good results were obtained with laser therapy and ultrasound therapy after the immobilisation period, using an ankle-brace with crutches and partial weight bearing on the affected limb even during the immobilisation period [23,26] and targeting physiotherapy on the muscular reinforcement of the peroneus longus and the brevis muscles starting after the immobilisation period [22,23,25,26,[31][32][33].…”
Section: Comparison Of Clinical Scoresmentioning
confidence: 99%